Nonindustrial Family Forest Landowners' Stated Willingness-to-Participate in Forest Cooperatives in Southern China - Lifei Yang; Yali Wen; Francisco X. Aguilar (International Journal of Forestry Research)
Forest landowner cooperatives have emerged as a formal institution capable of fostering professional forest management. There are many reasons to motivate participation in forest cooperatives. For instance, cooperatives could ease nonindustrial family forest landowners (NIFFLs) access to financial assistance and enhance market entrance opportunities. In China, various forms of forest cooperatives supported by government agencies are developing rapidly in an effort to facilitate forest management at a large scale. However, the development of forest cooperatives is still in its early stages. An understanding of NIFFLs' attitudes towards the development of cooperatives is instrumental for crafting policies and organizational structures that motivate landowners' participation. Three hundred and ten NIFFLs from Fujian and Jiangxi provinces in Southern China were interviewed to elicit their attitudes and willingness-to-participate in forest cooperatives. Logistic regression was used to evaluate landowner, household, forest resource, and institutional factors associated with NIFFLs' stated decision to participate in a forest cooperative. Results show that NIFFLs' stated willingness-to-participate in forest cooperatives was associated with demographic characteristics like education, forest-related income, size of forestland, and attitudes toward land tenure reform and cooperatives. This paper outlines suggestions on how to further develop forest cooperatives in Southern China.